О вероятности возникновения взрывов в помещениях, где используются бытовой газ и электрические сети 0,4/0,22 кВ - Ковалев, Александр Петрович; Москвина, Ирина Игоревна (НТУ "ХПИ", 2015)
На основе регулярных однородных марковских процессов с дискретным числом состояний и непрерывным временем, предложена математическая модель, с помощью которой возможно оценить взрывобезопасность помещений, в которых используется бытовой газ и сети 0,4/0,22 кВ с учетом: частоты появления взрывоопасной концентрации; длительности её существования; объема помещения; выделяемого объема газа; расхода воздуха в результате естественной вентиляции; изменения концентрации метана в течении времени; а также от частоты появления электрического источника поджигания и длительности его существования.

Explosion of gas-air mixture in the room, which uses natural gas and operated network of 0.4 / 0.22 kV can occur whenever the coincidence in time and space the following two random events: there was room explosive concentration of methane-air mixture; the room was damaged network and it appeared a source of ignition of 0.4 / 0.22 kV (short circuit, arcing at loose power contact connections, etc.). Based on regular homogeneous Markov processes with discrete number of states and continuous time, the mathematical model by which it is possible to estimate the explosion space, which use natural gas network and 0.4 / 0.22 kV, taking into account: the frequency of occurrence of an ex-plosive concentration of methane-air mixture ; the duration of its existence; volume of the space; volume of gas emitted from the damaged pipeline; air flow as a result of natural ventilation; changes in the concentration of methane in the course of time; as well as the frequency of occurrence of electrical ignition source and the duration of its existence. A new analytical dependence: the probability of occurrence of explosions in the room for a time t on the frequency of occurrence of an explo-sive methane-air mixture, its length of stay in a hazardous condition, the frequency of occurrence of the source of ignition and the duration of its ex-istence.
The possibility of explosions in areas where used household gas and electric networks 0.4 / 0.22 kV
Keywords: взрыв газа; метановоздушная смесь; взрывобезопасность; опасный электрический источник; марковские процессы; explosion of methane mixture; explosion; dangerous electrical source; Markov processes